Heterosis of leaf and rhizosphere microbiomes in field‐grown maize. Issue 3 (12th July 2020) - Wagner, Maggie R.; Roberts, Joseph H.; Balint‐Kurti, Peter; Holland, James B.
Summary: Macroorganisms' genotypes shape their phenotypes, which in turn shape the habitat available to potential microbial symbionts. This influence of host genotype on microbiome composition has been demonstrated in many systems; however, most previous studies have either compared unrelated genotypes or delved into molecular mechanisms. As a result, it is currently unclear whether the heritability of host‐associated microbiomes follows similar patterns to the heritability of other complex traits. We take a new approach to this question by comparing the microbiomes of diverse maize inbred lines and their F1 hybrid offspring, which we quantified in both rhizosphere and leaves of field‐grown plants using 16S‐v4 and ITS1 amplicon sequencing. We show that inbred lines and hybrids differ consistently in the composition of bacterial and fungal rhizosphere communities, as well as leaf‐associated fungal communities. A wide range of microbiome features display heterosis within individual crosses, consistent with patterns for nonmicrobial maize phenotypes. For leaf microbiomes, these results were supported by the observation that broad‐sense heritability in hybrids was substantially higher than narrow‐sense heritability. Our results support our hypothesis that at least some heterotic host traits affect microbiome composition in maize.